Disaster Capitalism within Aviation Industry: Putting Corporate Profits Ahead of Safety - Irsyadillah, Irsyadillah (International Journal of Disaster Management, 2023)
It is predicted that Indonesia will soon serve more than 140 million passengers a year. However, the safety records of the aviation industry have not shown a significant progress. Airlines operated in Indonesia has repeatedly experienced serious accidents killed hundreds of passengers and crew. The purpose of this study is to explore corporate communications related to safety culture. This study is concerned with the ideological role played by language in the discursive construction of safety culture. Using Thompsons (1990) schema regarding the modes of ideology, this study analyzes annual reports of two airlines operated in Indonesia published in the last fourteen years to establish the linguistic strategies used in their communications related to safety culture. The results suggest that the companies used particular linguistic strategies in their communication of safety culture to advance the worldviews of economic efficiency and cost control based on capitalist logic. The prioritization of business growth may contribute to avoiding allocating resources on aspect that is matter most. Given high expectation of safety standards of the aviation industry, the findings have clear and significant implications. It is recommended that aviation industry must improve their safety cultures to prevent unnecessary accidents in the future.